Language, music, and computing : first International Workshop, LMAC 2015, St. Petersburg, Russia, April 20-22, 2015, Revised selected papers /: first International Workshop, LMAC 2015, St. Petersburg, Russia, April 20-22, 2015, Revised selected papers. ([2015]) - Unknown
No abstract available